Embedding Sustainability in Engineering Education World Café: Reflections for Future Practice (UK and Ireland Engineering Education Research Network Conference Proceedings 2023, 2024)
We present the reflective learning account from organising a World Café to share engineering educators’ practices in embedding sustainability education, addressing the question: is the World Café a good practical solution to share sustainability education practice in our post pandemic world? Conversations have the power to create change, in line with approaches such as Critical Pedagogy (Giroux, 2020). Our perspective as diverse engineering educators informed the workshop and our reflections and this is mirrored in our analyses. The World Café is a process which has been extensively used to encourage open communication and problem solving (Brown, Isaacs and World Café Community, 2005) and which we thought relevant to enhancing sustainability education practices. A commitment to education for sustainable development (ESD) is increasingly expected (UNESCO, 2023; AdvanceHE and QAA, 2021) and engineering educators are rising to the challenge. Learning from one another, educators shared their actions, plans and dreams around the three pillars of sustainability. Using a Word Café to discuss challenges around sustainability education proved successful. We recommend that engineering educators and conference organisers consider this approach in creating a sense of urgency around sustainability that instigates collaboration and acts as a catalyst for action. The approach can be taken further by using it as a data collection tool, co-creating knowledge from our practice.